Jumping on the Bandwagon: Visualizing the Social Space of Social Taggers - Smiraglia, Richard (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
In social tagging, cultural forces lead to conformance. A study of tags from Delicious.com demonstrated a socially generated bandwagon effect. Here the effect is discussed in the context of Bourdieu’s notion of “social space” (1991). Social space of taggers provides boundary regions for cultural warrant in social classification. Dans l’étiquetage social, des forces culturelles poussent à la conformité. Une étude des étiquettes sur Delicious.com démontre un effet d’entraînement social. Dans la communication, cet effet est analysé dans le contexte de la notion « d’espace social » de Bourdieu (1991). L’espace social des étiqueteurs comporte des régions frontières au potentiel culturel dans la classification sociale.